Model Kebijakan Dividen : Analisis EPS, DER, Dan CR Terhadap Return Saham - Novya Fitri; Elfiswandi Elfiswandi; Ramdani Bayu Putra (MANAJEMEN, 2022)
Issues regarding stock returns are important for the company. Because stock returns are used as a measure of company performance by investors to invest in the stock market. This study aims to determine how the effect of EPS, DER, and CR on stock returns with dividend policy as an intervening variable in property & real estate companies listed on the Indonesia Stock Exchange. The sample in this study was taken by purpove sampling method on property & real estate companies listed on the IDX, namely 12 companies with a research period of 5 years from 2016-2020. The results of this study indicate that EPS, DER, and CR have a significant effect on dividend policy. EPS, DER, CR, and dividend policy have no significant effect on stock returns. Dividend policy is not able to mediate EPS, DER, CR to stock returns in property & real estate companies listed on the Indonesia Stock Exchange with a research period of 5 years from 2016-2020. Keywords : Current Ratio; Debt to Equity Ratio; Earning Per Share; Divident Policy; Stock Return.